Evaluating the ShakeOut drill in Aotearoa/New Zealand: Effects on knowledge, attitudes, and behaviour. (September 2020) - Vinnell, Lauren J.; Wallis, Amanda; Becker, Julia S.; Johnston, David M.
Abstract: Earthquakes pose a significant risk to Aotearoa/New Zealand (NZ), where many injuries occur during shaking. These negative outcomes can be reduced by teaching the protective action, 'Drop, cover, and hold'. The ShakeOut earthquake drill, developed in the United States to encourage practice of these protective actions, has been run nationwide in NZ in 2012, 2015, 2018, and 2019. Here we report an evaluation of the 2012 and 2015 ShakeOut drills. Previous research focuses on logistics of the drill, such as participation rates. In contrast, this study demonstrates that ShakeOut drill participants have better knowledge of correct protective actions, use of those actions during actual earthquake shaking, and additional preparedness actions, as well as weaker biases such as fatalism. In line with calls for more thorough evaluation of the behavioural and cognitive impacts of the drill, this research represents important preliminary evidence for meaningful benefits of employing ShakeOut.